No increased risk of hospitalization for heart failure for patients treated with dipeptidyl peptidase-4 inhibitors in Taiwan. (1st October 2016) - Chang, Chia-Hsuin; Chang, Yi-Cheng; Lin, Jou-Wei; Caffrey, James L.; Wu, Li-Chiu; Lai, Mei-Shu; Chuang, Lee-Ming
Abstract: Background: Saxagliptin has been reported to be associated with an increased risk of hospitalization for heart failure (HF). The objective of this study was to test whether the increased risk is drug specific or a class effect for dipeptidyl peptidase-4 (DPP-4) inhibitors. Methods: Diabetic patients prescribed sitagliptin, saxagliptin, and vildagliptin between 2011 and 2013 were identified from Taiwan's National Health Insurance (NHI) claims database. The outcome of interest was the first hospitalization for HF. The patients were followed for one year from drug initiation to outcome occurrence, death, or study termination (December 31, 2013). A Cox proportional hazards regression model was used to calculate the hazard ratios (HR) and their 95% confidence intervals, using sitagliptin as the reference group. Results: A total of 239, 669 patients, including 159, 330 sitagliptin, 38, 561 saxagliptin, and 41, 778 vildagliptin initiators, were included in the analysis. With a follow-up period ranging from 269 days (vildagliptin) to 313 days (sitagliptin), the crude incidence rate of HF was 2.77, 2.63, and 1.91 per 100 person-years for sitagliptin, saxagliptin, and vildagliptin, respectively. Saxagliptin had a similar risk (HR: 0.98, 95% CI: 0.91–1.06) to sitagliptin, while vildagliptin was associated with a lower risk of HF (HR: 0.85, 95% CI: 0.78–0.93). Auxiliary analyses using acarbose (n = 130, 800) as a reference group consistently showed no increased risk of HF associated with DDP-4 inhibitors. Conclusion: Three DPP-4 inhibitors studied seem to be safe regarding the risk of HF, while the reduced risk of vildagliptin might be a spurious association or a chance finding.